Gender and Politics: A Feminist Critique of the State - Sapkota, Mahendra; Dahal, Kabita (Journal of Political Science, 2022)
The relation between politics and gender is contentious, which is further implied in the feminist critique of the state. This paper assumes that the nature of the state is gendered. With this ontological position of critical worldview, it aims to synthesize the gendered nature of politics. Methodologically, it is based on the secondary literature and thus the authors did not offer their empirical data to synthesize the major arguments so far. It has first discussed the feminist theoretical debates about the worldview of the state and then offered the empirical issues of power and citizenship. It argues that the state is constructed with contradictions in terms of uneven allocation of resources, gendered institutions, androcentric leadership, and male-biased policies. In this context, the paper analyzes the state as an androcentric construction that is political, coupled with uneven gender relations. The authors also agree that politics eventually makes up the state - the supreme of power and hegemony against the women. The paper finally observes a need for further research works to critique the regimes, hegemony, and institutions of the state at the macro-level and identity, self-dignity, and citizenship of women in the state at the micro-level.